Carbothioamides as anticancer agents: synthesis, in-vitro activity, structure-activity relationship evaluations and molecular docking - Basharat Ali; Muhammad Riaz; Ajmal Khan; Nadir Rasheed; Muhammad Masood; Ali Iftikhar; Amir Faisal; Sobia Ahsan Halim; Jalal Uddin; Afnan Jan; Ahmed Al-Harrasi (Results in Chemistry)
Carbothioamides exhibit many biological properties, including antiviral, antibacterial and anticancer activities. Their ability to interfere with DNA synthesis is mainly responsible for their anticancer activities. Here, twelve phenyl-substituted carbothioamides (2−13) were synthesized and characterized using Electron Ionization Mass Spectrometry (EI-MS), proton and carbon-13 nuclear magnetic resonance (HNMR, and 13C NMR), Infrared (IR), and elemental analysis. The anticancer activity of the carbothioamide derivatives (2–13) was measured in the HCT116 colorectal cancer cell line by means of a three day sulforhodamine B (SRB) proliferation assay. Among the series, four compounds (2, 4, 11, and 12) which inhibited the cell viability by more than 50 % at 50 μM concentration. IC50 determination of these four compounds revealed 1-benzoyl-4-(2-bromophenyl) thiosemicarbazide (11) as the most potent compound with IC50 values of 21.61 ± 4.77 μM, 18.34 ± 3.53 μM and 17.87 ± 12.02 μM in the breast cancer (MCF-7) cell line, human colorectal carcinoma (HCT116) cell line and MD Anderson-metastatic breast (MDA-MB-453) cell lines respectively. Prolonged treatment of cells with the compound resulted in apoptotic cell death as determined by cleavage of Poly (ADP-ribose) polymerase (PARP), a caspase 3 substrate and an apoptotic marker. This study, therefore, explored novel derivatives of carbothioamides for their anticancer activities; the structure activity relationship (SAR) reported in this study and predicted docking analysis and ADMET profile will help optimize carbothioamides as anticancer agents.